THE IMPACT OF WEB-BASED APPLICATIONS ON ENGLISH LEARNING AMONG 4TH-GRADE STUDENTS - Muxlisa Rustamovna KAMOLOVA (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This study investigates how fourth-grade pupils in a primary school context can be taught English using web-based applications. Understanding how digital tools can help young learners improve their English language proficiency is the goal. Students used certain web-based tools, like Duolingo, Starfall, and British Council Kids, in their English classes over the course of four weeks. Teacher interviews, student feedback, and  classroom  observations  were  used  to  gather  data.  According  to  the  findings, students’  vocabulary  and  pronunciation  increased,  they  were  more  involved  in  the learning process, and they loved it. The apps were also helpful to teachers in developing engaging, student-focused lessons. In conclusion, web-based applications can be useful resources for helping young pupils in schools learn English, particularly when paired with conventional teaching techniques.